#TITLE_ALTERNATIVE# - FIRDAUS MULYADI, WILDAN
Hard chromium plating processes on steel substrate are usually carried out on some mechanical components that require high ductility but have high surface hardness for good wear resistance. For example on the manufacturing of a certain steel shaft that require a specific hardness inside, certain hard chromium coating thickness and high surface hardness on the outside. The shaft material used in this observation was a Low Carbon Steel, St-41. To obtain a good shaft quality, optimizing both parameters on hardening process and the hard chromium plating has been undertaken. The parameters on the hardening process were temperature and holding time, a hardness of 424 ± 42 VHN were achieved. The plating parameter observed were the effect of current density variation from 45 to 75 A/dm2 (Other parameters such as time; 30 minuetes, temperature 45oC and chromic acid concentration 225-275 g/L, were kept constant, this value were obtained from previous experiments on the plating process) on the thickness and hardness of the final surface of the shaft. A homogeneously hard chromium coating was observed from the experiment. A total surface hardness of 945 ± 47 VHN were obtained on the electroplated previously hardened shaft specimen employing 75 A/dm2 current density. A further experiment or characterization need to be carried out to have a more understanding on the mechanism controlling the total surface hardness. The precise mechanism should be further elaborated to ensure which one would have a dominant role such as the effect of internal strees introduced by Cr lattice distortion, impurities such as Fe, or the formation of chromium hydride on hard chromium grain.